Time-dependent evolution process of Sb2Te3 from nanoplates to nanorods and their Raman scattering properties - 孟秀清 汤宁 钟绵增 叶慧群 方允樟 (中国物理B：英文版, 2016)
High-quality Sb2Te3 nanostructures are synthesized by a simple hydrothermal method. The morphologies of the nanostructures change from hexagonal nanoplates to nanorods with the extension of growth time. Secondary nucleation is the dominant factor responsible for the change of the morphologies. Structural analyses indicate that all the obtained nanostructures are well crystallized. IR-active phonons are mainly observed in the Raman spectra of the nanoplates and nanorods. The slight deviations are observed in the Raman modes between the nanoplates and nanorods, which could originate from confinement effect in the nanostructures.